5
$\begingroup$

I recently came to know that there is a connection between Bures Fidelity $(F_B)$ and Quantum Fisher Information $(F_Q)$ given by

$$[F_{B}(\rho, \rho_\theta)]^2 = 1 - \frac{\theta^2}{4} F_Q[\rho, A] + O(\theta^3),$$ where $\rho_\theta = \exp(-iA\theta)\rho \exp(iA\theta)$ and $F_B(\rho_1, \rho_2) = \mathrm{Tr}\Big[ \sqrt{\sqrt{\rho_1}~ \rho_2~ \sqrt{\rho_1}}\Big]$.

How can one derive this result?

Here is the link to my source

$\endgroup$

1 Answer 1

4
$\begingroup$

Let $ \rho = \sum_n \rho_n |\psi_n \rangle \langle \psi_n | $ be the eigendecomposition of $\rho$. We will calculate everything in terms of $ |\psi_n \rangle$ basis.

Note that $ \frac{d \rho_\theta}{d \theta} = i [\rho_\theta, A] $ and $ \frac{d^2 \rho_\theta}{d \theta^2} = -\big[[\rho_\theta, A], A\big] $.

Now we write $$ \sqrt{ \sqrt{\rho} \rho_\theta \sqrt{\rho} } = \rho + \theta \cdot X + \theta^2 \cdot Y + O(\theta^3) \\ $$ for some matrices $ X, Y $ to be determined.

Squaring the above equation we get $$ \sqrt{\rho} \rho_\theta \sqrt{\rho} = \rho^2 + \theta \cdot (X \rho + \rho X) + \theta^2 \cdot (X^2 + Y \rho + \rho Y) + O(\theta^3) $$ This means that:

  • $ X \rho + \rho X = \sqrt{\rho} \frac{d \rho_\theta}{d \theta}\Big|_{\theta=0} \sqrt{\rho} = i \sqrt{\rho} [\rho, A] \sqrt{\rho} \implies \\ X_{nm} = i \frac{\sqrt{\rho_n \rho_m}}{\rho_n + \rho_m} \langle \psi_n | [\rho, A] |\psi_m \rangle = i \frac{\sqrt{\rho_n \rho_m}}{\rho_n + \rho_m} (\rho_n - \rho_m) \langle \psi_n | A |\psi_m \rangle $

and $ \text{Tr}[X] = \sum_n X_{nn} = 0 $.

Similarly:

  • $ Y \rho + \rho Y + X^2 = \sqrt{\rho} \frac{d^2 \rho_\theta}{d \theta^2}\Big|_{\theta=0} \sqrt{\rho} = -\sqrt{\rho} \Big[[\rho, A], A\Big] \sqrt{\rho} \implies \\ Y_{nm} = - \frac{(X^2)_{nm}}{\rho_n + \rho_m} - \frac{\sqrt{\rho_n \rho_m}}{\rho_n + \rho_m} \langle \psi_n | \Big[[\rho, A], A\Big] |\psi_m \rangle $

and $ \text{Tr}[Y] = \sum_n Y_{nn} = - \sum_n \frac{(X^2)_{nn}}{2\rho_n} - \frac{1}{2} \text{Tr}\Big[\big[[\rho, A], A\big]\Big] = - \sum_n \frac{(X^2)_{nn}}{2\rho_n} = - \sum_{n,k} \frac{X_{nk}X_{kn}}{2\rho_n} \\ = - \frac{1}{2} \sum_{n,k} \frac{\rho_k}{(\rho_n + \rho_k)^2} (\rho_n - \rho_k)^2 |\langle \psi_n | A |\psi_k \rangle|^2 \\ = - \frac{1}{4} \sum_{n,k} \frac{\rho_k}{(\rho_n + \rho_k)^2} (\rho_n - \rho_k)^2 |\langle \psi_n | A |\psi_k \rangle|^2 - \frac{1}{4} \sum_{n,k} \frac{\rho_n}{(\rho_n + \rho_k)^2} (\rho_n - \rho_k)^2 |\langle \psi_n | A |\psi_k \rangle|^2 \\ = - \frac{1}{4} \sum_{n,k} \frac{(\rho_n - \rho_k)^2}{\rho_n + \rho_k} |\langle \psi_n | A |\psi_k \rangle|^2 = -\frac{1}{8} F_Q[\rho, A] $.

Finally: $ F_B(\rho, \rho_\theta) = \Big(\text{Tr}\big[\sqrt{ \sqrt{\rho} \rho_\theta \sqrt{\rho} } \big]\Big)^2 = \Big(\text{Tr}\rho + \theta^2 \cdot \text{Tr}Y + O(\theta^3) \Big)^2 = \\ \Big(1 - \theta^2 \frac{F_Q[\rho, A]}{8} + O(\theta^3) \Big)^2 = 1 - \theta^2 \frac{F_Q[\rho, A]}{4} $

$\endgroup$
0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.